Miswak: Awareness and knowledge amongst Malaysian dental educators - Che Musa, Muhd Firdaus (2018)
Aims: To examine the level of awareness and knowledge on the use of miswak and its role in oral health from the perspective of educators in one international dental school in Malaysia and make recommendations for the future research/health policy. Materials and methods: A qualitative research of focus group was conducted amongst dental educators at Kulliyyah of Dentistry, International Islamic University of Malaysia. Up to four focus groups were carried out (n=4 for each group) during 2017. The first group comprising local and Muslim educators; (2) local and non-Muslim; (3) international and Muslim; and (4) international and non-Muslim. The focus groups using a topic guide to explore the miswak/miswak teaching and its best practice in oral health. Focus groups were recorded, transcribed and analysed using Framework Analysis. Results: Research with the dental educators (n=20) identified generally same level of awareness on the use of miswak in general; and specifically in teaching following their post-education/ training and knowledge which is limited, restricted, and localised. The awareness leads to either low or high of miswak practice that is further supported by four identified initiators domains namely self-care, teaching, research and policy-politics. Conclusion: Educators’ views metaphorically on the level of awareness/knowledge on the use of miswak given they are Asian and Muslim respondents with secular/western educational background. A broad and flexible strategy is required to overcome an issue of ignoring this established and proven methods of miswak in oral hygiene practice for the benefit of healthcare systems and the population.